The Government's Role in Improving The Business Performance Of Exporters In Bali - I Gde Wedana Arjawa; Ni Nengah Ganawati; Putu Ayu Sita Laksmi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The government has an important role in improving the business performance of exporters in Bali Province. By involving these various aspects, the government can make a significant contribution in improving the business performance of exporters in Bali Province, facilitating economic growth and creating jobs. This research was conducted in Bali Province with a population of 237 people and 70 respondents. Results from tests for validity and reliability are accurate and reliable. The results of hypothesis testing show that business performance is significantly and positively influenced by the role of the government. This study shows how the role of the government is carried out well can improve the business performance of exporters in Bali Province.